EFEKTIFITAS PELATIHAN KECERDASAN EMOSIONAL UNTUK MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS REMAJA PANTI ASUHAN - Rebecca Wijaya; Gazhella Stefy Putri; Lena Nessyana Pandjaitan (Program Studi S1 Psikologi, 2020)
This study aims to improve psychological well-beimg of adolescents Harapan orphanage through emotional intelligence training. Emotional Intelligence aspects in this study are perceiving emotion, facilitating thought with emotion, understanding emotion, and managing emotion. The concept of this training is experiencing learning. Material of training taught and delivered through lecturing, games, discussion, writing task, reflection, role play, presentation, and self record. Participants are 14 teenage boys who lived in HA Orphanage. The design chosen for this study was one-group pretest-posttest design. The result of quantitative analysis was significant differences before and after training. It showed that emotional intelligence training was effective to improve psychological well-being of teenage boys Harapan’s orphanage.